Muscarinic M1 receptors stimulated by intracerebroventricular administration of McN-A-343 reduces the nerve injury-induced mechanical hypersensitivity via GABAB receptors rather than GABAA receptors in mice - Keisuke Migita; Akiko Nishimura; Fumihiro Eto; Kohei Koga; Taichi Matsumoto; Kazuki Terada; Shuji Hara; Kenji Honda (Elsevier, 2020)
Cholinergic neurons play an important role in the higher functions of the brain, such as the memory, cognition, and nociception. However, the exact mechanism behind how the stimulation of all the muscarinic M1 receptors in the entire brain results in the alleviation of partial sciatic nerve ligation (PSNL)-induced mechanical hypersensitivity has not been investigated. Thus, we examined which subtype of GABA receptor was involved in the alleviation of PSNL-induce mechanical hypersensitivity produced by an intracerebroventricular administration of a muscarinic M1 receptor agonist, McN-A-343. Administering a GABAA receptor antagonist, bicuculline, resulted in no changes to the McN-A-343-induced anti-hypersensitivity in PSNL mice whereas a GABAB receptor antagonist, CGP35348, dose-dependently inhibited the anti-hypersensitivity. Furthermore, CGP35348 increased mechanical hypersensitivity in naïve mice, and the hypersensitivity was blocked by NMDA receptor antagonists, MK-801 and D-AP5. Additionally, muscarinic M1 receptors colocalized with GABAB1 receptors and an NMDA receptor subunit, GluN2A, in a large region of the brain. Consequently, these results suggest that the activation of muscarinic M1 receptors in the entire brain reduces nerve injury-induced mechanical hypersensitivity via the GABAB receptors, and the activation of the GABAB receptors regulates glutamatergic transmission via NMDA receptors. Keywords: Muscarinic M1 receptor, GABAB receptor, NMDA receptor, Intracerebroventricular administration, Partial sciatic nerve ligation model